Intellectual Property Management System (IPMS) - Omar, Muhammad Rashidin (Universiti Teknologi PETRONAS, 2011)
Intellectual Property can be defined as the permission to control the use of certain intangible expression and ideas in a form of entitlement, for an individual. For many reasons, intellectual property or IP has been playing a major role in many organizations that promote invention and innovation. The reason of having a good IP practise is to ensure the idea and work of one particular inventor or innovator will be secure from infringement and plagiarism. In Malaysia especially, many organizations still don't have a good IP practise. Those companies tend to neglect the necessity of having their idea protected and secured. In order to fulfil the needs of having a simple system that can help organizations to promote a good IP practise, Intellectual Property Management System or IPMS came into the picture. The purpose of this system is to act as a hub that can help organizations to smoothen the procedure of patenting within the premise. Traditional ways are normally can be related to the use of paper and pen. Inventors and innovators have to fill a 5-page of form and have to wait for a long period of time before their idea being approved by the employer. There are many risks when using the traditional way. The papers went missing, misplaced, tear apart; there are all the risks that might occur.